On endoscopic p-adic automorphic forms for SL2 - Ludwig, Judith (Documenta mathematica, 2018)
We show the existence of some non-classical cohomological $p$-adic automorphic eigenforms for $\SL_2$ using endoscopy and the geometry of eigenvarieties. These forms seem to account for some non-automorphic members of classical global $L$-packets.